2021
DOI: 10.1002/fut.22263
|View full text |Cite
|
Sign up to set email alerts
|

Lottery and bubble stocks and the cross‐section of option‐implied tail risks

Abstract: The options smile provides forward‐looking information about the risk at the center of the distribution (ATM‐IV) and at the tails (Skew). We investigate the cross‐sectional determinants of the options smile using indices that capture firm fundamental risks, heterogeneity in belief, lottery characteristics, and bubble characteristics. We find that at‐the‐money (ATM) volatility is explained mainly by historical risks and predicted future risks measured using accounting‐based risk measures and firm characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 80 publications
1
4
0
Order By: Relevance
“…To remove outliers, we winsorize all of our variables at the 1st and 99th percentile. The average Volatility RND for our sample is 0.38, which is very close to the average IV value of ATM options reported in the Indian market by previous studies (Agarwalla et al, 2022). The mean value of Skew RND is − 0.12, confirming the finding in the literature that option-implied RND is typically negatively skewed.…”
Section: Summary Statisticssupporting
confidence: 87%
See 3 more Smart Citations
“…To remove outliers, we winsorize all of our variables at the 1st and 99th percentile. The average Volatility RND for our sample is 0.38, which is very close to the average IV value of ATM options reported in the Indian market by previous studies (Agarwalla et al, 2022). The mean value of Skew RND is − 0.12, confirming the finding in the literature that option-implied RND is typically negatively skewed.…”
Section: Summary Statisticssupporting
confidence: 87%
“…The SSO and SSF prices are obtained from the NSE trade book with matching time-stamped quotes, and the volume data are taken from the NSE BHAV files. Following Jain et al (2019) and Agarwalla et al (2022), we applied various filters to the options price data. First, we removed options contracts that traded for less than (any) 5 min on a day.…”
Section: Indian Sso Marketmentioning
confidence: 99%
See 2 more Smart Citations
“…For this, we use the Fama and MacBeth (1973) regression, wherein we regress the monthly average of these variables over lagged IMIN and other control variables. Prior papers have found that stocks' market beta, systematic risk, BbyM , size, idiosyncratic skewness of the stock returns, analyst dispersion and coverage, put‐to‐call ratio, and momentum can explain the cross‐sectional variation in the ATM‐IV and IVSKEW (Agarwalla et al, 2022; Bollen & Whaley, 2004; Dennis & Mayhew, 2002; Duan & Wei, 2009; Feng et al, 2018). We have included these variables as control variables.…”
Section: Analysis Of the Potential Channelsmentioning
confidence: 99%